2003
DOI: 10.1021/ic0342393
|View full text |Cite
|
Sign up to set email alerts
|

DFT Studies of Uranyl Acetate, Carbonate, and Malonate, Complexes in Solution

Abstract: The aim of this work is to demonstrate that theoretical chemistry can be used as a complementary tool in determining geometric parameters of a number of uranyl complexes in solution, which are not observable by experimental methods. In addition, we propose plausible structures with partial geometric data from experimental results. A gradient corrected DFT methodology with relativistic effects is used employing a COSMO solvation model. The theoretical calculations show good agreement with experimental X-ray and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 63 publications
10
53
0
Order By: Relevance
“…As simple and common organic ligand, carboxylic acids can form strong complexes with actinide cations. Various dioxouranium(VI) carboxyl complexes have been studied by using EXAFS and QM methods . The carboxyl ligands of these species exhibit bidentate and monodentate coordination.…”
Section: Actinide Computational Chemistry Associated With Exafs and Xmentioning
confidence: 99%
“…As simple and common organic ligand, carboxylic acids can form strong complexes with actinide cations. Various dioxouranium(VI) carboxyl complexes have been studied by using EXAFS and QM methods . The carboxyl ligands of these species exhibit bidentate and monodentate coordination.…”
Section: Actinide Computational Chemistry Associated With Exafs and Xmentioning
confidence: 99%
“…These studies consist in QM cluster calculations with none, one, or two explicit hydration shells treated at various levels of theory (Pyykkö et al, 1994;Hemmingsen et al, 2000;Tsushima et al, 2002;Kubicki et al, 2009). Some of the studies also add a water continuum model (Gagliardi et al, 2001;Vásquez et al, 2003;Austin et al, 2009). The calculated U-O CO 2À Docrat et al, 1999;Bernhard et al, 2001;Elzinga et al, 2004;Ikeda et al, 2007a).…”
Section: Structural and Dynamical Hydration Propertiesmentioning
confidence: 99%
“…For Ca 2 UO 2 ðCO 3 Þ 3 , QM cluster calculations at the DFT level of theory with varying numbers of explicit water molecules, and in some cases a water continuum model, resulted in U-O CO 2À 3 distances from 2.36 to 2.84 Å and U-Ca distances ranging between 3.83 and 4.05 Å (Tsushima et al, 2002;Vásquez et al, 2003;Kubicki et al, 2009). EXAFS data of Bernhard et al (2001) and Kelly et al (2007) yielded U-O CO 2À 3 distances of 2.44 and 2.45 Å , respectively, and UCa distances of 3.94 and 4.02 Å , respectively.…”
Section: Structural and Dynamical Hydration Propertiesmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20] On the theoretical side, there has been a large increase in the number of computational investigations of actinide complexes, particularly those of uranium. [22][23][24][25][26][27][28][29][30][31] The electronic structure and molecular geometry of the di-oxo cation of the three elements U, Np, and Pu have been studied at the Hartree Fock (HF), 26 density functional theory (DFT) 23,24,27,29 as well as correlated ab initio levels. 22,28 In addition to the requirement of using high levels of theory and basis sets, modelling actinide ions is also quite challenging because of the need to account for solvation and relativisitic effects at some level.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Vazquez et al modeled the uranyl acetate, carbonate and malonate complexes of uranyl in solution using DFT. 31 We have recently investigated the interaction of uranyl with functionalized carbon nanotubes and found that the binding of uranyl is strong in the functionalized case than the unfunctionalized counterpart. 32 Hence, there is need for further calculations in order to understand in more details the binding behavior of uranyl with nanostructures, which might help us in designing new nanomaterials that can be efficiently used for nuclear waste management.…”
Section: Introductionmentioning
confidence: 99%